1998
DOI: 10.1074/jbc.273.45.29530
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of Energy Metabolism of the Heart during Acute Increase in Heart Work

Abstract: The normal programmed development of a multicellular organism from the germ cell is a synchronized series of events driven by genetic instructions acquired during conception. During the early critical periods in life the organism also has the ability to respond to environmental situations that are alien to normal development by adaptations at the cellular, molecular, and biochemical levels. Such early adaptations to a nutritional stress/stimulus permanently change the physiology and metabolism of the organism … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

14
266
2
1

Year Published

2003
2003
2024
2024

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 290 publications
(287 citation statements)
references
References 53 publications
14
266
2
1
Order By: Relevance
“…2C), even in the absence of an increase in arterial lactate concentration, which is similar to the relative increase we previously measure for oxidation of exogenous glucose and fatty acids in pigs subjected to a three-to fourfold increase in MV O 2 (20,26,36). Thus the heart increases its reliance on carbohydrate oxidation with increased cardiac work, as demonstrated in previous experimental studies in humans and pigs (16,30,36) and in the isolated perfused rat heart (12,17). Moreover, model simulations predicted a greater rate of lactate uptake and pyruvate oxidation as a function of increased arterial lactate concentration, which resulted in inhibition of fatty acid oxidation.…”
Section: Discussionsupporting
confidence: 86%
“…2C), even in the absence of an increase in arterial lactate concentration, which is similar to the relative increase we previously measure for oxidation of exogenous glucose and fatty acids in pigs subjected to a three-to fourfold increase in MV O 2 (20,26,36). Thus the heart increases its reliance on carbohydrate oxidation with increased cardiac work, as demonstrated in previous experimental studies in humans and pigs (16,30,36) and in the isolated perfused rat heart (12,17). Moreover, model simulations predicted a greater rate of lactate uptake and pyruvate oxidation as a function of increased arterial lactate concentration, which resulted in inhibition of fatty acid oxidation.…”
Section: Discussionsupporting
confidence: 86%
“…20 However, several studies have suggested that increased glucose oxidation alone is insufficient for cardiac energy demands during stress. Total β-oxidation was increased by 40% when heart work was acutely increased, 21 and suppression of cardiac FA oxidation in peroxisome proliferator activated receptor (PPAR)-γ coactivator-1α knockout mice resulted in accelerated pressure-overload HF. 22 Augustus et al 23 reported that LPL knockout (hLpL0) hearts were susceptible to HF because of loss of LPL-mediated triglyceride lipolysis and low CPT-1 expression.…”
Section: Discussionmentioning
confidence: 99%
“…This dichotomy may be due to the different features of the study groups. It is recognized as a dominance of fatty acid metabolism by the heart in the fasted state; when the heart is acutely stressed, it switches from fat to carbohydrates as fuel (25) because of a more convenient balance of oxygen consumption. In fact, artificial elevation of FFA in diabetic hearts reduces cardiac efficiency via an oxygen waste for noncontractile purposes (26).…”
Section: Effects Of Hemodynamic and Metabolic Variables On The Correlmentioning
confidence: 99%